Indoor air quality in a dentistry clinic - Helmis, C.G.a; Tzoutzas, J.b; Flocas, H.A.a; Halios, C.H.a; Stathopoulou, O.I.a; Assimakopoulos, V.D.c; Panis, V.b; Apostolatou, M.a; Sgouros, G.a; Adam, E.b (Science of the Total Environment, 2007)
The purpose of this work is to assess, both experimentally and theoretically the status of air quality in a dentistry clinic of the Athens University Dentistry Faculty with respect to chemical pollutants and identify the indoor sources associated with dental activities. Total VOCs, CO2, PM10, PM2.5, NOx and SO2 were measured over a period of approximately three months in a selected dentistry clinic. High pollution levels during the operation hours regarding CO2, total VOCs and Particulate Matter were found, while in the non-working periods lower levels were recorded. On the contrary, NOx and SO2 remained at low levels for the whole experimental period. These conditions were associated with the number of occupants, the nature of the dental clinical procedures, the materials used and the ventilation schemes, which lead to high concentrations, far above the limits that are set by international organizations and concern human exposure. The indoor environmental conditions were investigated using the Computational Fluid Dynamics (CFD) model PHOENICS for inert gases simulation. The results revealed diagonal temperature stratification and low air velocities leading to pollution stratification, accompanied by accumulation of inert gaseous species in certain areas of the room. Different schemes of natural ventilation were also applied in order to examine their effect on the indoor comfort conditions for the occupants, in terms of air renewal and double cross ventilation was found to be most effective. The relative contribution of the indoor sources, which are mainly associated with indoor activities, was assessed by application of the Multi Chamber Indoor Air Quality Model (MIAQ) to the experimental data. It was found that deposition onto indoor surfaces is an important removal mechanism while a great amount of particulate matter emitted in the Clinic burdened severely the indoor air quality. The natural ventilation of the room seemed to reduce the levels of the fine particles. The emission rates for the fine and coarse particulates were found to be almost equal, while the coarse particles were found susceptible to deposition onto indoor surfaces. © 2007 Elsevier B.V. All rights reserved.
Keywords: air conditioning; Air Pollutants; Air pollution; air pollution control; Air quality; ambient air; article; carbon dioxide; chemical pollutant; Computational fluid dynamics; dental clinic; Dental Clinics; Dentistry; emission; environmental conditions; Environmental Monitoring; exposure; Greece; Indoor; indoor air; Indoor air pollution; Indoor air quality; inert gas; Models; Nitric oxide; Nitrogen oxides; nitrous oxide; occupational exposure; Organic Chemicals; Particulate emissions; Particulate matter; Particulate matters; pollutant; pollution exposure; priority journal; simulation; Sulfur dioxide; temperature; Theoretical; Ventilation; volatile organic compound; Volatile Organic Compounds